Moral Education Values In The Anime Film One Piece Arc, Dressrosa Perspective Of Immanuel Kant In The Book Of Moral Laws - Nur Laily Alfiatul Izza; Kustiana Arisanti; Ainur Rofiq Sofa (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyse the moral educational values depicted in the One Piece anime, specifically within the Dressrosa Arc, through the lens of Immanuel Kant’s philosophical framework as articulated in his work The Moral Law. The rationale for this research stems from the growing importance of employing popular media as an educational medium to cultivate moral awareness among younger generations, particularly within the context of Islamic religious education. A qualitative approach was adopted, utilising the library research method. Data were gathered through the examination of episodes from the Dressrosa Arc accessed via digital platforms such as Telegram and Bstation, and were subsequently analysed in conjunction with relevant literature, including Kant’s philosophical texts, scholarly journals, and academic e-books. The data were analysed using a descriptive narrative method encompassing data reduction, categorisation, interpretation, and conclusion drawing. The findings indicate that the Dressrosa Arc conveys key moral values such as honesty, moral courage, justice, and respect for human dignity. These values are consistent with Kantian principles that emphasise duty-based ethics and adherence to universal moral laws. Within the framework of Islamic education, such values possess the potential to contribute significantly to the development of morally upright and socially responsible individuals